Sanitation Management Chain Policy in Tangerang City - Dafyar Eliadi (Universitas Teuku Umar, 2023)
The increasing population growth in Tangerang City impacts environmental management related to domestic wastewater. This research was conducted because previously, it was found that there were problems in wastewater management in Tangerang City. This study aims to analyze the policies in domestic wastewater management in Tangerang City. The problem of this research is analyzed by public policy theory, based on the content and actor approach of public policy. The method used in this research is qualitative research. The data was obtained from several sources, such as primary and secondary data. The primary data consists of interviews with informants, which a purposive technique has decided. The results of this study explain that the Tangerang City Government applies the SPALD-S and SPALD-T strategies in the sanitation management chain in Tangerang City. The existence of a service function is not optimal because the service orientation needs to try to maximize its function. Then, public access to information is separate from socialization and education programs. This study concludes that the sanitation management provided by the relevant agencies is still faced with several obstacles, such as service orientation that has not been maximized, the lack of public access to information on management services, and the infrastructure of the sanitation management chain, which is considered insufficient.